Implementation of contextual learning to strengthen the character of gotong royong and understanding of Toraja culture in elementary schools - Harmelia Tulak; Alexander Pakiding; Topanus Tulak; Natalya Banne (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Globalization has weakened the younger generation's attachment to local culture, including the value of mutual cooperation, which is a crucial part of character education. Elementary schools play a strategic role in reinstilling these values through contextual, meaningful learning. The Tongkonan concept is presented as a learning innovation based on Toraja culture to strengthen students' character and cultural understanding from an early age. This research aims to strengthen the character of mutual cooperation and increase students' understanding of Toraja culture as part of local identity. The research method uses a quantitative approach with a one-group pre-test-post-test quasi-experimental design. The research subject was grade VI elementary school students. Core activities include a miniature Tongkonan-making project and a field visit to the Tongkonan site. This program involves teachers and local community leaders as companions to the activity. Data collection techniques include participatory observation, pre- and post-tests, interviews, and assessment of student activity results. The results of the study show that contextual learning grounded in Toraja culture is effective in strengthening elementary school students' character and understanding of Toraja culture, fostering mutual cooperation.